Estimation of frequency of radar signals with continuous emission for short sample length of realization based on processing of quadrature decomposition - M. V. Ronkin; A. A. Kalmikov; E. I. Khrestina (Известия высших учебных заведений России: Радиоэлектроника, 2015)
The new algorithm for fast estimation of short signals realization is presented. The proposed algorithm involve processing of linear frequency modulation signals by evaluation-correlator scheme, quadrature decomposition, and digital processing of relation between phase and time. The comparisons with estimation of frequency in spectral domain depend on signal to noise ratio and on delay have been performed.